Phytochemical study, antioxidant and anticonvulsant activities of aqueous extract of leaves of Opilia celtidifolia (guill. Et perr.) Endl. Ex walp. Opiliaceae, from Benin. - DASSOU, Gbèwonmèdéa Hospice; GLINMA, BIENVENU; ASSOGBA, Fidèle M..; AKAKPO, B. Huguette; Toklo, Placide Mahougnan; AHOTON, Djidénou; KPOVIESSI, Salomé S. D.; Ladékan Yayi, Eléonore; Gbenou, Joachim D (My University, 2022)
Epilepsy is a chronic neurological disease in developing countries. The access to appropriate care for the management of this disease being difficult in our countries, a large number of patients resort to the use of medicinal plants including Opilia celtidifolia. To contribute to the scientific knowledge of this plant and to promote the development of phytomedicines, we evaluated its antioxidant and anticonvulsant properties. The phytochemical screening of the aqueous extract of its leafy stems showed flavonoids (flavones), reducing compounds, anthocyanins, leuco-anthocyanins, saponosides, triterpenoids and mucilages. By spectrophotometric assays, total polyphenols and flavonoids were quantified. The extract was rich in total polyphenols and flavonoids with contents of 89.712 mg GAE/g extract and 37.040 mg QAE/g extract respectively. The antiradical activity was evaluated in vitro by DPPH test. The free radical scavenging activity gave an IC50 of 0.29 mg/mL. In a pharmacological model of epilepsy induced by pilocarpine (method developed and validated in Wistar rats), the administration of Opilia celtidifolia extract demonstrated the ability of this plant to significantly delay the onset of convulsions, to significantly reduce their intensity and to protect the rats from death precipitated by the violence of the convulsions. Finally, the larval toxicity of the extract was evaluated in vitro on Artemia salina and showed non-toxic activity (IC50> 0.1 mg/mL). Although these preliminary results, obtained on the basis of animal experiments, are not immediately extrapolable to humans, they constitute a pharmacological argument in favor of the traditional use of the plant for the management of epilepsy
Keywords: Phytochemical screening; anticonvulsivant activity; antioxidant; toxicity; Opilia c.